2018
DOI: 10.6007/ijarbss/v8-i11/4986
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Autonomous Use of Technology for Language Learning Among ESL Learners at Tertiary Level

Abstract: Acknowledging the importance of autonomous language learning with technology as an essential skill for lifelong learning, the current study was carried out to investigate whether a group of tertiary level ESL learners were able to self-direct their use of technology for effective language learning experience. The mixed-methods approach was employed to understand the phenomenon. Findings indicate that the most preferred Web 2.0 technology for language learning is the online exercises/quizzes. This is followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Effective English learning must encourage students’ interest in actively exploring language knowledge with technology for autonomous language learning (Rahamat et al , 2017; Zulkepli et al , 2018). In this study, the use of broadcast technology provided an interactive self-learning opportunity for ESL.…”
Section: Discussionmentioning
confidence: 99%
“…Effective English learning must encourage students’ interest in actively exploring language knowledge with technology for autonomous language learning (Rahamat et al , 2017; Zulkepli et al , 2018). In this study, the use of broadcast technology provided an interactive self-learning opportunity for ESL.…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al [39] attested that threedimensional virtual game-based environments could boost Taiwanese elementary school students' English vocabulary knowledge, learning collaboration, and autonomy. Finally, Zulkepli and colleagues [40] surveyed 289 Malaysian freshman students about their Web 2.0 tools' preference for autonomous language learning. It was found that the students favored conventional technologies specifically designed for language learning, such as online quizzes and discussion forums.…”
Section: Autonomous Use Of Technology For Second-language Learningmentioning
confidence: 99%
“…Even both formal and informal learners are also now assessing learning materials through Internet and websites (Mc Greal, 2018). In Malaysian context, Malaysian Communications and Multimedia Commission has revealed that youths between the (Zulkepli, et al, 2018). Advantages of using Information and Communication Technology (ICT) and technology in learning and teaching session were reported to be beneficial in attracting students' attention, facilitating students' learning process, helping to improve students' vocabulary and also promoting meaningful learning to students.…”
Section: Literature Review Massive Open Online Courses (Moocs) In Thementioning
confidence: 99%